A possible India : essays in political criticism - Chatterjee, Partha (Delhi ; Oxford University Press, 1997)
Post 1947 political situation in India.
Includes bibliographical references and index.
Includes English translation of articles in Bengali.
Keywords: India -- Politics and government -- 1947-